Analysis of the possibilities of using renewable sources to achieve nearly zero-energy consumption in residential buildings - Zlateva Merima; Totev Totyo (E3S Web of Conferences)
This research paper presents results of a study and analysis of energy consumption in typical residential buildings with different percentages of heated area of the total floorage depending on the climatic conditions of the region of their location and their operating modes. The energy characteristics and energy consumption in the buildings are determined using a calculation method adopted as regulatory in Bulgaria. Different options for heat supply using energy from renewable sources - solar radiation, ambient air and groundwater, are considered. The performance of the systems for utilizing the potential of renewable energy sources is modelled and simulated using a validated software product, and the results obtained are analysed in order to determine the possibilities for achieving near zero energy consumption depending on the climatic conditions and the specific construction and structural features of the buildings.